2019
DOI: 10.2147/ndt.s202432
|View full text |Cite
|
Sign up to set email alerts
|

<p>Fear of cancer recurrence, anxiety and depressive symptoms in adolescent and young adult cancer patients</p>

Abstract: Background: Previous studies have indicated that younger age is consistently associated with high levels of fear of cancer recurrence (FCR), anxiety and depression. However, the associations among these variables in adolescent and young adult (AYA) cancer patients are not clear. This study explores the prevalence and correlates of FCR, anxiety and depressive symptoms in Chinese AYA cancer population. Methods: This is a cross-sectional study that includes 249 patients aged bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 47 publications
(53 reference statements)
4
84
0
3
Order By: Relevance
“…A Case Record Form (CRF) was designed for this study to collect generic demographic and clinical information, such as gender, age, education level, marital status, employment status, personal monthly income, treatment/family history, physical comorbidities, lifestyle (smoking and exercise), and previous experience. Experience of adversity in childhood and experience of severe illness were assessed by two yes/no questions ( 15 ): 1) Have you ever experienced any childhood adversity, such as sexual abuse, bullying, traffic accident, or natural calamities? 2) Have you ever experienced any severe illness during childhood, such as childhood cancer, or traumatic injury?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Case Record Form (CRF) was designed for this study to collect generic demographic and clinical information, such as gender, age, education level, marital status, employment status, personal monthly income, treatment/family history, physical comorbidities, lifestyle (smoking and exercise), and previous experience. Experience of adversity in childhood and experience of severe illness were assessed by two yes/no questions ( 15 ): 1) Have you ever experienced any childhood adversity, such as sexual abuse, bullying, traffic accident, or natural calamities? 2) Have you ever experienced any severe illness during childhood, such as childhood cancer, or traumatic injury?…”
Section: Methodsmentioning
confidence: 99%
“…A recent review reported a wider range of percentages between 0.8 and 71.4% of suicidal ideation in cancer patients, compared to a range of 1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].8% in the general population (11). Another review, involving 44 relevant studies indicated that the prevalence of suicidal ideation ranged from 0.8 to 46.2% among cancer patients; with lowest figures being reported by an American study while the highest percentage was reported in Chinese samples (12).…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, el distrés psicológico y MRC se asociaron con la CDVRS en las pacientes sobrevivientes de cáncer de mama. Lo que indica que al experimentar niveles elevados distrés y de MRC, la CDVRS global se deteriora, tal como se ha reportado en estudios previos (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) . Algunos estudios (22,32) , reportaron que las pacientes sobrevivientes con cáncer de mama con una mejor CDVRS presentan mejor funcionamiento físico, emocional y social y una menor incidencia de MRC y distrés psicológico.…”
Section: Discussionunclassified
“…De acuerdo al perfil sociodemográfico de las pacientes, que indicó que la mayoría de ellas se encuentran en edades activas, en tiempo menor a 5 años de supervivencia, frecuentemente madres, solteras, aunque laboralmente activas, de bajo nivel socioeconómico y sin estudios superiores, son factores importantes que pueden mantener los niveles de distrés psicológico y de MRC, tal como se ha reportado en algunos estudios (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) . Se sabe que la interacción entre factores biológicos y psicosociales relacionados al cáncer pueden desbordar los recursos de afrontamiento de los pacientes oncológicos y dar lugar a respuestas emocionales que pueden desarrollarse en un continúo que va del distrés común hasta desórdenes de ajuste, de ansiedad o depresión (45) .…”
Section: Discussionunclassified
See 1 more Smart Citation